Estimation of Ordinary Kriging Method with Jackknife Technique on Rainfall Data in Malang Raya - Novia Nur Rohma (International Journal on Information and Communication Technology (IJoICT), 2022)
Geostatistics is a science that focuses on spatial data. In geostatistics, there is an estimation method to handle variables whose values ​​vary with the change in location or place, which are called regionalized variables. The estimation method used to handle regionalized variables is called the kriging method. In the ordinary kriging method it is necessary to take into account the semivariogram. Rain is a process of falling water from the clouds to the earth. Rain is measured through rainfall. The purpose of this study was to determine estimation of the ordinary kriging method on normally distributed data and abnormally distributed data, and determine the best semivariogram. The data used is monthly rainfall data in Malang Raya for the period January 2016 to December 2016. From the monthly rainfall dataset, the data are normally distributed in January, February, March, April, May, June, August, September, October, November and December 2016, while the data are not normally distributed in July. Ordinary kriging with Jackknife method can be used to analyze data with normal distribution and data with abnormal distribution.